The Li-adsorbed C(100)-(1x1): O Diamond Surface - O'Donnell, Kane; Martin, T.; Fox, N.; Cherns, D. (Cambridge University Press, 2011)
This paper presents density functional theory results for the Li-adsorbed C(100)-(1x1):O system. Previously it has been shown that at a single monolayer coverage, the binding energy for Li on oxygenated C(100) diamond is substantially higher than that of heavier alkali metals, while at the same time, the presence of the lithium generates a large shift in the diamond workfunction. The system is therefore promising for electronics applications involving diamond. Here, further calculations are presented showing that additional Li atoms above 1ML coverage are far less strongly bound, suggesting the 1ML surface is the most useful for vacuum microelectronic applications.